2019
DOI: 10.26675/jabe.v3i2.5757
|View full text |Cite
|
Sign up to set email alerts
|

Stress Exposure and Psychological Well-being: Study on Beginning Teacher

Abstract: A beginning teacher is someone who has just started his/her career as a teacher or someone who has just graduated from college and is working as a teacher. This transition from student to worker (as a teacher) is a critical period since it is often associated with stress (Dicke et al., 2015; Smith and Ingersoll 2004). This study examines the relationship between stress exposure (seen from stress exposure in class and outside class) and the psychological well-being of beginning teachers (seen from work enthusia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our assumption was deducting from the previous studies. As we know, TRC is a form of job demands, and the previous studies showing that job demands reduce work enthusiasm [29,30,34], and work enthusiasm also been noted to increase teacher work performance [37]. The others also found that work engagement, which indicates work enthusiasm, mediates the link between job demands and job outcomes [38].…”
Section: Occupational Well-being As the Mediatormentioning
confidence: 92%
See 1 more Smart Citation
“…Our assumption was deducting from the previous studies. As we know, TRC is a form of job demands, and the previous studies showing that job demands reduce work enthusiasm [29,30,34], and work enthusiasm also been noted to increase teacher work performance [37]. The others also found that work engagement, which indicates work enthusiasm, mediates the link between job demands and job outcomes [38].…”
Section: Occupational Well-being As the Mediatormentioning
confidence: 92%
“…The occupational well-being of teachers refers to the optimum condition of psychological and work experience [28]. It is indicated from the presence of job satisfaction and work enthusiasm, also the absence of stress and emotional exhaustion in the teaching activity [29][30][31]. We concentrate on emotional exhaustion and work enthusiasm to accommodate the positive and negative dimensions of occupational well-being.…”
Section: Occupational Well-being As the Mediatormentioning
confidence: 99%
“…Moreover, psychological well-being is often seen from work enthusiasm and psychological exhaustion experienced by someone (Aldrup et al, 2017; M. Arief . Positive things mark an optimal psychological condition, and work experience (Ryan & Deci, 2001;Zacher et al, 2015) felt or experienced by someone, such as the job satisfaction, excitement, and the absence of adverse experiences such as stress and emotional fatigue (Diener et al, 1999;Kunter et al, 2008;M. Arief Rafsanjani & Rahmawati, 2019;Watson et al, 1988).…”
Section: Theoretical Support Psychological Well-beingmentioning
confidence: 99%
“…The most dominant factor is stress exposure at work. Many studies explain that stress exposure received at work harms one's psychological well-being (Aldrup et al, 2017;Duygulu et al, 2013;Kyriacou, 2011;M. Arief Rafsanjani & Rahmawati, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of variable, one of the dominant factors is associated with the exposure to stress at work. Previous researches show that teacher psychological well-being is influenced by exposure to stress in the workplace (Aldrup, Klusmann, & Lüdtke, 2017;Duygulu, Ciraklar, Guripek, & Bagiran, 2013;Kyriacou, 2011;Rafsanjani & Rahmawati, 2019). One of the dominant causes of stress for teacher is student misbehavior (Aldrup, Klusmann, Lüdtke, Göllner, & Trautwein, 2018;Kyriacou, 2011).…”
Section: Introductionmentioning
confidence: 99%